Three smart girls [videorecording (DVD)] - Koster, Henry, 1905-1988; Durbin, Deanna; Barnes, Binnie, 1903-1998; Brady, Alice, 1892-1939; Milland, Ray; Winninger, Charles, 1884-1969 (Universal Studios Home Entertainment, 2012)
Three sisters attempt to reunite their mother and father who divorced a decade ago. The girls decide to pay their millionaire father a surprise visit in New York when they learn of his intentions to remarry. The object of his current affections is headed for disaster when the girls arrive to break up the romance and bring their father home.